PERAN BADAN USAHA MILIK KAMPUNG (BUMKAM) TENGGEKAHWANG DALAM MENINGKATKAN PENDAPATAN MASYARAKAT KAMPUNG BRONGKENDIK, KABUPATEN FAKFAK - Braweri, Ilham; Fitanto, Bahtiar (Journal of Development Economic and Social Studies, 2023)
Fakfak Regency has MSMEs engaged in the Nutmeg Agro-industry sector. One of the products that was successfully made was Balm Nutmeg. Nutmeg balm is made from nutmeg fat and several types of herbs grown by fakfak farmers. Fakfak Nutmeg Balm is a brand of balsam produced by BUMKam (Village-Owned Enterprises) Kampung Brongkendik. BUMKam was founded in 2017 and was only active as an entrepreneur in October 2020. The research aims to find scientific facts related to science. The research method has a meaning, namely the sequence or procedure of the researcher to find answers to the problems posed by the researcher, so to find answers to the problems posed by the researcher using a qualitative approach method. The results of the study show that four indicators measure the role of BUMKam in increasing people's income such as product, price, distribution and promotion in Brongkendik Village, Fakfak District. The role of BUMKam in increasing the income of the people in Brongkendik Village, Fakfak Regency by looking at the product dimension indicators can be said to have not been fully implemented because even though the quality of the nutmeg balm product is very adequate and of good quality, in terms of packaging it still has not received a patent packaging design and is still changing. -change